Efficacy of different hypertonic solutes in the treatment of refractory intracranial hypertension in severe head injury patients: A comparative study of 2ml/kg 7.5% hypertonic saline and 2ml/kg 20% mannitol - Chatterjee, Nilay; Chaudhury, Arpan; Mukherjee, Sujoy; Prusty, Gouri Kumar; Chattopadhyay, Tapas; Saha, Subhasis (Indian Journal of Neurotrauma, 2007)
A prospective, randomized study to evaluate the clinical benefit of increasing the osmotic load of the hypertonic solution administered for the treatment of refractory intracranial hypertension episodes in patients with severe head injury. 25 patients with severe head injury and persistent coma, admitted in a Neurocritical Care Unit of a Tertiary Care Hospital, who required infusions of osmotic agents to treat episodes of intracranial hypertension resistant to well defined standard modes of therapy were randomly allocated to one of the two groups to receive isovolume infusions of either 7.5% hypertonic saline solution; HS [2400 mOsm/kg H2O] or 20% mannitol [1160 mOsm/kg of H2O] given 2ml/kg of either solution, i.e. 331.5 +/− 35.4 mOsm of hypertonic saline or 174.2 +/− 18 mOsm of mannitol per infusion. The variables recorded in the study were the duration and number of episodes of intracranial hypertension per day during the study period, which was stopped after the last episode of intracranial hypertension was recorded from intracranial pressure recording or after the allocated treatment failure. Patients of HS group were monitored for 7 +/− 6 days and those in the mannitol group for 8 +/− 5 days [p=NS]. The rate of failure for each treatment was also evaluated which was defined as the persistence of intracranial hypertension despite the two successive infusions of the same osmotic agent. The mean number of osmotic solute infusions was 3.4 +/− 4.5 in the HS group and 3.8 +/− 5.1 in mannitol group p=NS]. The mean number [7.1+/-2.9 vs. 14.6+/−3.4] of episodes of intracranial hypertension per day and the duration of such episode [62.6+/−28.1 vs. 93.4+/−37.2 min] was also significantly lower in the HS group [p<0.05]. The numbers of treatment failures were significantly lower in HS group: 1 out of 14 patients vs. 6 out of 11 patients [p<0.01]. In this study we have found that in patients with severe head injury requiring treatment with hypertonic solute for refractory intracranial hypertension, 2ml/kg body weight of 7.5% HS [356 +/− 14 mOsm] was more effective than giving 2ml/kg 20% mannitol [178 +/− 11mOsm]. Within the limitations of present study, the collected data suggest that giving 2ml/kg HS solution is an effective and safe initial treatment for intracranial hypertension episodes in head injury patients when there is indication of osmotherapy.
Keywords: Intracranial Hypertension; Mannitol; Hypertonic Saline; Head Injury